PENGARUH SOSIAL MEDIA, CITRA MEREK DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN DI SATE KHAS SENAYAN - Kurniawan, Mega Utami; Ruliarto, Heidi Reza (PT Naureen Digital Education, 2025)
This research was conducted with the aim of analyzing the influence of social media, brand image, and product quality on purchasing decisions at Sate Khas Senayan. To achieve this objective, the research method employed the use of SPSS (Statistical Package for the Social Sciences) version 24 software and purposive sampling method. The research sample consisted of 120 respondents who were customers of Sate Khas Senayan. The findings of this study indicate that social media, brand image, and product quality have a significant influence on purchasing decisions.